Aplikasi Analisis Pemberian Reward Tenaga Pendidik Menggunakan Metode Fuzzy Relation - Ramadhani, Nilam; Syahroni, Abd. Wahab; Darmawan, Irwan; Maula, Ismatul (Universitas PGRI Kanjuruhan Malang, 2024)
Analysis of rewards gift with fuzzy relations aims to determine teachers who deserve accept rewards based on teacher performance assessments. Fuzzy relations are used to determine the level of relationship or relations between criteria with rating weights that have been determined objectively. The aspects assessed include 4 criteria, that is pedagogic, personality, professionalism, and social relations. Each criterion has a different number of sub-criteria. Overall there are 26 sub-criteria and 45 teachers from 6 elementary schools are assessed.The results of the performance assessment of 45 teachers with fuzzy relations and weighting criteria obtained one teacher data that has the highest performance value among other teachers. So that the value obtained is used as a decision support to determine which teacher is entitled and deserves a reward.